PENGEMBANGAN MODEL PEMBELAJARAN DISKUSI DAN PERSONAL INVESTIGATION DALAM PEMBELAJARAN SEJARAH KELAS XI IPS DI SMA MUHAMMADIYAH ENDE FLORES - Wasa, Damianus Rikardo Sumbi (LPPM Institut Pendidikan Nusantara Global, 2023)
History learning at school, the learning model used by teachers is still felt to be very lacking in class XI IPS at SMA Muhammadiyah Ende Flores. The learning model used by teachers is just the same, resulting in students' activeness and independence in learning increasingly decreasing. Therefore, it is necessary to develop a new learning model that can stimulate the activity and independence of students in class XI IPS at SMA Muhammadiyah Ende Flores in learning, namely the discussion and personal investigation learning model. This research uses RnD (Research and Development) which is a research method used to produce certain products and to test the effectiveness of these products. Researchers focus on developing discussion and personal investigation learning models which are intended to be able to develop a new learning model that can be applied in learning with clear steps according to scientific principles. The results of research on the development of discussion and personal investigation learning models in learning are as follows: (1) students are more active in learning, (2) students no longer rely on friends when there are assignments or discussions, (3) students can analyze problems that occur in learning easily. , (4) can foster a sense of responsibility in each student, especially responsibility as a group member, (5) with this learning model the learning process in class is more enjoyable.